PROCESS APPROACH OF DIGITAL ECONOMY AS A BASIS FOR SOLVING INNOVATIVE, ECONOMIC, SOCIAL PROBLEMS - N. Kharchenko (Вестник Северо-Кавказского федерального университета, 2022)
According to modern digital models of interaction, the development of dialogue between business and the state is one of the priority directions of state policy in this area. At the legislative level, a number of basic mechanisms of interaction between business and the state are enshrined: public advisory councils, the institution of appeals, the activities of business unions and associations, etc. Nevertheless, as the results of the expert discussion showed, the situation in the sphere of interaction between the authorities and business structures does not contribute to the development of effective use and a full-fledged bilateral dialogue between business and the state.